Magnetic Resonance Imaging and Its Benefit in Epilepsy and Seizure Disorders Diagnosis (Iraqi Journal of Medical Sciences, 2024)
Background: Brain magnetic resonance imaging (MRI) is one of the most important investigations in epilepsy, which can detect any structural abnormality such as infarctions, gliosis, tumors and other different abnormalities.Objective: To investigate types of structural brain lesions and its relation to their seizure semiology.Methods: This is a retrospective cross-sectional study involving 352 patients. Collected data were taken from patient’s files in epilepsy clinic between 2016-2021. Sequences were used according to MRI epilepsy protocols.Results: Files of 352 patients were reviewed, males 222 (63.1 %) while the rest were females (36.9 %), mean age of patients was 30.69 years ± 11.011 and mainly from the age group 18-30 years old (57.1%). Regarding the clinical diagnosis of seizure 210 (59.65%) to have focal type seizures and 142 (40.35%) of the patients with generalized types. One-third of seizure subtypes was a generalized tonic-clonic seizure (32.1%), followed by focal aware seizure (19.3%), focal to bilateral tonic-clonic (15.6%). Regarding MRI findings, (62%) of the patients had a normal study, temporal lobe pathology 32 (9.1%) patients, gliosis 21 (6%) patients, generalized brain atrophy was 15 (4.3%) patients, nonspecific white matter lesion was 10 (2.8%) patients, cerebrovascular insult was (2.8%).Conclusion: The commonest MRI findings in epileptic patients was normal scan, followed by mesial temporal lobe lesions, gliosis, nonspecific white matter lesions, brain atrophy and cerebrovascular insults.Keywords: Epilepsy, MRI, seizure, tonic-clonicCitation: Obaid HH, Jabbar BH, Salman BH. Magnetic resonance imaging and its benefit in epilepsy and seizure disorders diagnosis. Iraqi JMS. 2024; 22(2): 291-297. doi: 10.22578/IJMS.22.2.14
Keywords: Epilepsy; MRI; seizure; tonicclonic